The nature of the photo luminescence in amorphized PZT - Silva, M. S.; Cilense, M.; Orhan, E.; Goes, M. S.; Machado, MAC; Santos, LPS; Paiva-Santos, C. O.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Zaghete, M. E.; Pizani, P. S. (Elsevier B.V., 2005)
The polymeric precursor method was used to synthesize lead zirconate titanate powder (PZT). The crystalline powder was then amorphized by a high-energy ball milling process during 120h. A strong photoluminescence emission was observed at room temperature for the amorphized PZT powder. The powders were characterized by XRD and the percentage of amorphous phase was calculated through Rietveld refinement. The microstructure for both phases was investigated by TEM. The optical gap was calculated through the Wood and Tauc method using the UV-Vis. data. Quantum mechanical calculations were carried out to give an interpretation of the photoluminescence in terms of electronic structure. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: photoluminescence; amorphous; CRYSTAL98